Convincing Industry that there is Value In Environmentally Supply Chains - Sarkis, Joseph (Problemy Ekorozwoju, 2009)
The article is focused on ESCM – environmentally sustainable supply chain management. The main question is: how can organizations develop a ‘business case’ for valuing the practice? The answer goes far beyond environmental and technical improvements.